Accounting for the new gains from trade liberalization - Chang-tai Hsieh; Nicholas Li; Ralph Ossa; Mu-jeung Yang (University of Zurich, Department of Economics, 2017)
We measure the "new" gains from trade reaped by Canada as a result of the Canada-US Free Trade Agreement (CUSFTA). We think of the "new" gains from trade of a country as all welfare effects pertaining to changes in the set of firms serving that country as emphasized in the so-called "new" trade literature. To this end, we first develop an exact decomposition of the gains from trade which separates "traditional" and "new" gains. We then apply this decomposition using Canadian and US micro data and and that the "new" welfare effects of CUSFTA on Canada were negative.
Keywords: F10; F12; F14; 330; Gains from trade; trade liberalization; CUSFTA